(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
The effective insertion of the pharmacist into primary care is an important goal for health policies. The objective of this study was to describe and analyze pharmacists and Pharmaceutical Care in the primary health centers (UBS) of São Bernardo do Campo. Data were obtained through an interview applied to pharmacists. The instrument has three sections: (1) Pharmacist identification; (2) Pharmacist work; and (3) Pharmaceutical activities. Items in section 3 correspond to the guidelines of agencies that promote Pharmaceutical Care in the primary health system. All 24 pharmacists working in UBS in São Bernardo do Campo were interviewed. Every center dispensing medicines has a responsible pharmacist. These pharmacists are predominantly women and postgraduates. Activities of Pharmaceutical Care reported were: daily prescription analysis (75% of interviewees); monthly participation in patient groups (70.8%); monthly follow-up of pharmacotherapy adherence (58.3%); monthly participation in multiprofessional team meetings (54.2%); monthly home visits (12.5%); health education to the community (83.3%); and pharmacist consultation (37.5%). Frequency of prescription analysis and home visits was weakly associated with aspects of the pharmacist and the facility. This study showed that Pharmaceutical Services are structured in primary care in São Bernardo do Campo and many Pharmaceutical Care activities are offered in its UBS.